Uma modelagem de indicadores de desempenho para instituições de ensino superior no Brasil na abordagem do balanced scorecard: um estudo com instituições privadas - Campos, Ronald Fábio de Paiva (2008)
This Master of Science Thesis deals with a BSC modeling for higher education institution focusing on private institution in the Brazilian context. It‟s accomplished a literature review in order to understand the BSC and its application to for profit and non for profit organizations and as a main result it is proposed a BSC conceptual model with a new perspective (Government) and a change in the hierarchy of the main BSC perspective equaling financial to customer/society. Taking the national higher education assessment system of Education Ministry indicators a model is deployed and the relations between the indicators are measured with the Pearson correlation coefficient. As a result a model emerges with sound relations of indicators but a improvement in the financial indicators is needed